Homoacetogenic Conversion of Mannitol by the Thermophilic Acetogenic Bacterium Thermoanaerobacter kivui Requires External CO2 - Moon, Jimyung; Jain, Surbhi; Müller, Volker; Basen, Mirko (Frontiers in Microbiology, 2020)
Acetogenic microorganisms utilize organic substrates such as sugars in addition to hydrogen (H2) + carbon dioxide (CO2). Electrons from the oxidation of organic substrates are still removed by CO2 reduction through the Wood-Ljungdahl pathway (WLP), a process which has been called “homoacetogenesis” with respect to the fermentation of sugars. But how are more reduced substrates such as the sugar alcohol mannitol metabolized? Are acetogens then restricted to utilize additional carbon dioxide (CO2) or can they utilize protons as electron acceptors, similar to some fermentative microorganisms? Recently, we reported that the thermophilic acetogenic microorganism Thermoanaerobacter kivui is among the few acetogens that utilize mannitol, dependent on a gene cluster encoding mannitol uptake, phosphorylation and oxidation of mannitol-1-phosphate to fructose-6-phosphate. Here, we studied mannitol metabolism with resting cells of T. kivui; and found that mannitol was “fermented” in a homoacetogenic manner, i.e. acetate was the sole product if HCO3– was present. We found an acetate:mannitol ratio higher than 3, indicating the requirement of external CO2, and the involvement of the WLP as terminal electron accepting pathway. In the absence of CO2 (or bicarbonate, HCO3–), however, the cells still converted mannitol to acetate, but slowly and with stoichiometric amounts of H2 formed in addition, resulting in a “mixed” fermentation. This showed that – in addition to the WLP – the cells used an additional electron sink – protons, making up for the “missing” CO2 as electron sink. Growth was 2.5-fold slower in the absence of external CO2, while the addition of formate completely restored the growth rate. A model for mannitol metabolism is presented, involving the major 3 hydrogenases, to explain how [H] make their way from glycolysis into the products acetate or acetate+H2.